Characteristics of liquid sugar from old oil palm trunk sap as affected by processing methods - Nurdjanah, Siti; Hasanudin, Udin; Setiyoko, Febri; Yuliandari, Puspita; Nawansih, Otik; Utomo, Tanto Pratondo (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2024)
The sap of old oil palm trunks contains appreciable sugar, but it has not been considered a potential sugar source. This study aimed to find the best method for producing oil palm liquid sugar that complies with the Indonesian National Standard (SNI) The non-factorial experiment was arranged in a Completely Randomized Block Design (CRBD) with 6 replications. The treatments were a combination of lime-rotary vacuum evaporation (P1), without lime-vacuum rotary evaporation (P2), lime-atmospheric evaporation (P3); without lime-atmospheric evaporation (P4). The parameters observed were pH, °brix, reducing sugar, color, aroma, and overall acceptance. The data were subjected to ANOVA to determine the effects of the treatments and then, continued testing using HSD at α 0,05 for means separation. The best treatment was found on liquid sugar processed using lime, and atmospheric evaporation with brix of 68.75%, pH of 5.4, moisture content of 17.74, ash content of 0.86%, reducing sugar of 44.31%, sensory score of color, aroma, and overall acceptance were f 3.42 (brownies yellow), 4.4 (like), and 4.04 (like).Keywords: lime, liquid sugar, old oil palm trunk, sensory, vacuum rotary evaporator